2019
DOI: 10.1039/c9se00029a
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the tolerance of marine yeast to inhibitory compounds for improving bioethanol production

Abstract: Inhibitor tolerance is one of the key challenges in lignocellulosic bioethanol production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 40 publications
1
24
0
Order By: Relevance
“…Furfural affected conidial germination and subsequent colony development in a dose-dependent manner with an IC 50 ~ 12.5 mM, as measured 20 h post inoculation (Additional file 1: Figure S1A). The inhibitory value we measured was similar to the IC 50 of 16 mM measured for S. cerevisiae [38].…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…Furfural affected conidial germination and subsequent colony development in a dose-dependent manner with an IC 50 ~ 12.5 mM, as measured 20 h post inoculation (Additional file 1: Figure S1A). The inhibitory value we measured was similar to the IC 50 of 16 mM measured for S. cerevisiae [38].…”
Section: Resultssupporting
confidence: 85%
“…In this study, we focused on the ascomycete fungus N. crassa as a potential source of genes for yeast strain improvement. This fungus is able to grow on burned trees and is thus exposed to the inhibitory compound furfural in its natural habitat [25], even though the IC 50 for furfural was similar in N. crassa and yeast [38]. To understand the molecular and metabolic basis and to identify new genes involved in tolerance toward furfural in N. crassa, we used a combination of approaches, including RNA-seq, hypothesis-driven reverse genetics and random promotor insertional mutagenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Current industrial probiotic microbial strains are predominantly isolated from terrestrial environment. It has been reported that marine yeasts are phenotypically distinct for terrestrial yeasts and highly tolerant to growth inhibitors such as salt, acid, and temperature [71]. Marine microorganisms, especially marine yeasts, have shown interesting probiotic properties [72, 73].…”
Section: Discussionmentioning
confidence: 99%
“…The conventional method for producing BNC using glucose as carbon source is a high cost process and cannot be produced on large industrial scale. Therefore, production of BNC using cheap industrial waste as carbon, nitrogen and energy sources is required and has been extensively studied 20 – 23 . Coffee cherry husk extract (a byproduct from the coffee processing) 21 was used as less expensive source of carbon and a lot of other wastes like waste from fruit processing 22 .…”
Section: Introductionmentioning
confidence: 99%